Le coût humain des pesticides : comment les viticulteurs et les techniciens viticoles français font face au risque - Christian Nicourt; Jean Max Girault (VertigO, 2009)
Through a corpus of 70 interviews carried out with vine growers and vine advisers in Languedoc-Roussillon, our aim was to understand why the vine growers do not seek to solve their uncertainties on the medical consequences in relation to the use of pesticides. Our assumption is that it is the only strategy offered to them to control their fear in their work. First, we show that they consider in an ambiguous way the evils which affect them during their work. Second, we analyze their difficulties to preserve their health in a context of constrained work. Third, we examine how conducts of challenge and a denial of the situations are articulated to enable the continuation of their work. That, when public evaluation gives paradoxical messages, in a context of destructuration of spaces and time-sharings between vine growers, involves a racking of collectives, while rural areas are recombining. This erodes the strategies of defense of the wine growers and does not moderate their pesticides use, but modifies their methods.